Molecular and morphological investigations of two new species in Qinia and Cymbella (Bacillariophyceae: Cymbellales) from China. - Jingshen Li; Andrei Mironov; Yutong Jiang; Jinyan Liang; John P Kociolek; Yevhen Maltsev; Yawen Fan; Yan Liu; Maxim Kulikovskiy (PLoS ONE)
Molecular data is provided firstly for the newly erected genus Qinia, and the phylogenetic position of the genus Qinia within the Cymbellales is discussed. Despite the presence of apical pore fields bisected by the distal raphe fissure being a very distinctive feature for Qinia, molecular analysis demonstrates this character as homoplasious, having evolved independently in Qinia and Cymbella. Two new species, Qinia hubeii sp. nov. and Cymbella wuhanensis sp. nov., are described based on multigene molecular investigation (genetic markers 18S rDNA, 28S rDNA and rbcL) and morphological comparisons with the diatoms from the family Cymbellaceae. Molecular data suggest a close relationship between Qinia hubeii sp. nov. and Karthickia and Encyonopsis, while Cymbella wuhanensis sp. nov. forms a clade with Cymbella aspera and Cymbella bengalensis. Morphological features of the new species were observed with light and scanning electron microscopy. Comparison of Qinia hubeii sp. nov. with other species in Qinia and Cymbella wuhanensis sp. nov. with similar Cymbella species were discussed.